2008
DOI: 10.1258/jtt.2008.080313
|View full text |Cite
|
Sign up to set email alerts
|

Quality of diabetes care among patients managed by teleconsultation

Abstract: We studied a new teamwork-based teleconsultation model for treating patients with diabetes, where a specialist in diabetes care, a diabetes nurse and a patient attended by videoconference. The study series consisted of all the patients (n = 101) at three health centres in northern Finland whose care was provided by a single physician at a remote diabetes clinic. A total of 101 patients with diabetes (19 of type 1 and 82 of type 2) were studied at baseline and at 10-14 months after the first consultation. Mean … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 31 publications
0
11
0
Order By: Relevance
“…VCs increase the possibility for ‘just in time diagnosis’ from specialist when there is no waiting time for visit by referral. It has been used in different settings and contexts in health care, for example, ophthalmology (Bergua et al ., 2009), endocrinology/diabetes management (Nikkanen et al ., 2008), cardiology (Boman et al ., 2009), dermatology (Edison et al ., 2011), and in psychiatry (Stain et al ., 2011). Another example is when a patient asks for a second opinion from another specialist physician (Törnqvist et al ., 2000; Visser et al ., 2010).…”
Section: Introductionmentioning
confidence: 99%
“…VCs increase the possibility for ‘just in time diagnosis’ from specialist when there is no waiting time for visit by referral. It has been used in different settings and contexts in health care, for example, ophthalmology (Bergua et al ., 2009), endocrinology/diabetes management (Nikkanen et al ., 2008), cardiology (Boman et al ., 2009), dermatology (Edison et al ., 2011), and in psychiatry (Stain et al ., 2011). Another example is when a patient asks for a second opinion from another specialist physician (Törnqvist et al ., 2000; Visser et al ., 2010).…”
Section: Introductionmentioning
confidence: 99%
“…HbA 1c levels appeared uncompromised over time in intervention groups compared to standard diabetes care, relative to either control or baseline values. All but two of the quantitative studies included in this review reported significant reduction in HbA 1c 23–26,28,29,31,33 . Maxwell et al .…”
Section: Resultsmentioning
confidence: 91%
“…All but two of the quantitative studies included in this review reported significant reduction in HbA1c. [23][24][25][26]28,29,31,33 23,31 The remaining three studies found there to be no significant change in LDL level at follow-up. 24,25,27 A significant decrease in overall cholesterol level was found by Rasmussen et al 28 Blood pressure.…”
Section: Study Findings: Quantitative Outcomes Of Interestmentioning
confidence: 94%
See 1 more Smart Citation
“…Of the 92 studies included, 98 different intervention groups were isolated: 17 NC, 3244,46,47,55,65 46 MNF, 45,48,64,66–74,7690,137 and 35 NNI. 75,91,93…”
Section: Resultsmentioning
confidence: 99%